2021
DOI: 10.3389/feart.2021.653395
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features and Evolution of the Northwestern Sichuan Basin: Insights From Discrete Numerical Simulations

Abstract: The northwestern Sichuan Basin has experienced Meso-Cenozoic intracontinental compressional tectonic processes and formed multi-detachment stratigraphic distribution of foreland basins and fold-thrust belts, which have caused complicated structural deformations in the deep buried layers. Rapid uplift with accelerated erosion and two sets of detachments in the Lower Triassic and Lower Cambrian controlled the multilevel deformation structure. We conducted discrete numerical simulations with double weak detachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Both the regional geological structure analysis and the structural simulation experiments show that if there is a regional distribution of salt rock as an important dĂ©collement layer in the fold orogenic belt and its foreland basin, the strata will undergo obvious structural stratification deformation in the vertical direction (Figures 5, 6) (Wang et al, 2010;Yin et al, 2011;Xu et al, 2012;Wu et al, 2014;Yang, 2017;Neng et al, 2018;Li, 2019;Li et al, 2020;Sun et al, 2021;Xu et al, 2021). The results of these experiments well reflect the regional structural characteristics of the northern margin of the western Kuqa Depression (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the regional geological structure analysis and the structural simulation experiments show that if there is a regional distribution of salt rock as an important dĂ©collement layer in the fold orogenic belt and its foreland basin, the strata will undergo obvious structural stratification deformation in the vertical direction (Figures 5, 6) (Wang et al, 2010;Yin et al, 2011;Xu et al, 2012;Wu et al, 2014;Yang, 2017;Neng et al, 2018;Li, 2019;Li et al, 2020;Sun et al, 2021;Xu et al, 2021). The results of these experiments well reflect the regional structural characteristics of the northern margin of the western Kuqa Depression (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The discrete element method (DEM) has been applied to the study of geological and geophysical problems in recent decades (Hardy et al, 2009;Yin et al, 2009;Liu et al, 2015;Morgan, 2015;Botter et al, 2016;Buiter et al, 2016;Morgan and Bangs, 2017;Li, 2019;Li et al, 2020;Xu et al, 2021). A full, detailed description of the theory behind this modeling approach and its application to geological problems is given by Morgan (2015) and Li C. et al (2017Li C. et al ( , 2018Li C. et al ( , 2021, Li (2019).…”
Section: Experimental Methods and Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the thick‐skinned imbricate thrust fault system has been forming under a compressive environment since the late Miocene. This interpretation scheme is determined by the comprehensive analysis of the structural and sedimentary evolution, structural modelling, structural quantitative calculation and balanced cross‐section restoration (Gao, 2020; He et al., 2023; Li et al., 2016; Wang et al., 2017; Wu et al., 2014; Xu et al., 2021; Yin et al., 2011). Previous studies (Guo et al., 2010; Qi et al., 2009; Yang et al., 2018) have suggested that the high‐angle basement‐involved faults are regional extensional faults that developed in the Jurassic–Early Cretaceous extensional environment also support this interpretation scheme.…”
Section: Characteristics Of Preexisting Structures In the Kuqa Depres...mentioning
confidence: 99%
“…The western Sichuan Depression is located in the western part of the Sichuan Basin in China. It was developed based on the foreland basins in the western Sichuan Basin starting in the Late Triassic and represents the most developed area of continental natural gas in the Sichuan Basin (Xu et al, 2021). The western Sichuan Depression is a long strip zone extending in a NE-SW direction, and it is divided into north, middle, and south sections by the Mianzhu-Fenggu line and the Dayi-Chengdu line.…”
Section: Geological Backgroundmentioning
confidence: 99%